THE EFFICIENCY OF THE THROWS-IN UNDER THE BOARD IN BASKETBALL - Onose I.; Petrea R.G (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Basketball is a rich game in techniques, with a variety of tactical actions, presenting tendencies of universalism by requiring players with advanced technical training to meet the demands of the game. The issue of training and development of the tactical thinking is a factor to which special attention must be given in training athletes and in the game, but also in training the future teachers and coaches in basketball. Tactics is an active contribution in the game of reason, seeking to capitalize on the preparation of the players and of the team, taking into account the opponent's weaknesses. So, using the moments when the attacking team, in the game of basketball, is around the adverse basket, there is a great probability to obtain favorable situations for marking points which may contribute to the final victory. For this reason in the 30 lessons allocated on the fixed moments of the game we are using a large number of repetitions, modern tools and complex, simplify situations during matches. Were also selected six tactical combinations of throwing the ball under adverse panel that have demonstrated effectiveness in the two games check. It was found that the optimal approach to reinstatement under adverse panel leads to effective fixed moments of the game achieving the objectives in the offensive basketball: marking as many points.